ZIF-derived non-noble metal electrocatalyst and preparation method thereof
By converting carbon atoms into nitrogen atoms in H3BTT·2HCl, the ZIF-derived non-precious metal electrocatalysts are solved, and the problems of high cost and insufficient catalytic activity of non-precious metal electrocatalysts in the prior art are achieved, and efficient ORR catalytic activity and cost reduction are achieved .
Patent Information
- Application Number
- CN202411567184.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
In the prior art, when non-precious metal electrocatalysts are used in cathode oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs), the cost is high and the catalytic activity is insufficient, which limits the large-scale commercial application of fuel cells.
By converting carbon atoms in H3BTT·2HCl into nitrogen atoms, ZIF-derived non-precious metal electrocatalysts are prepared, and high-density nitrogen atomic active sites and porous carbons are formed by ultraviolet irradiation, ozone oxygen mixed gas treatment and thermal cracking. Skeleton, improve catalytic activity.
It has achieved the reduction of PEMFCs costs, improved the ORR catalytic activity of non-precious metal electrocatalysts, enhanced the content of nitrogen elements and the formation of active sites, and promoted the efficient energy conversion of fuel cells.
Smart Images

Figure CN119419294A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of fuel cell technology, and in particular relates to a ZIF-derived non-precious metal electrocatalyst and a preparation method thereof. Background Art
[0002] Among the existing technologies, polymer electrolyte membrane fuel cells (PEMFCs) are considered to be the most promising alternative to internal combustion engines. Unlike internal combustion engines, PEMFCs provide high energy conversion efficiency and power density at relatively low operating temperatures, and have zero or low greenhouse gas emissions. Compared with platinum (Pt)-based electrocatalysts, non-precious metal-based electrocatalysts have attracted widespread attention due to their lower cost. The development of high-performance non-precious metal electrocatalysts for cathode oxygen reduction reaction (ORR) is crucial for the large-scale commercial application of PEMFCs.
[0003] Among various non-precious metal electrocatalysts, transition metal nitrogen carbon (MNC) catalyst research is the most competitive. The synthesis method of this type of catalyst is simple and flexible, the price is low, and it exhibits excellent ORR catalytic activity under acidic conditions. In order to obtain high-performance non-precious metal electrocatalysts, it is key to regulate the active site density and framework structure during the synthesis process. Nitrogen is an important component of the active site, and the framework structure includes the structural position of the transition metal and nitrogen, as well as the structure of the carbon carrier. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a ZIF-derived non-precious metal electrocatalyst and a preparation method thereof, which can reduce the cost of PEMFCs.
[0005] According to the ZIF-derived non-precious metal electrocatalyst of the first embodiment of the present application, S1: H3BTT·2HCl and chloroform are added to a container under a protective atmosphere, and m-chloroperbenzoic acid is added dropwise to the container to obtain a first liquid; S2: The container is sealed, kept warm at 40°C to 60°C, and the first liquid is stirred for 15 to 20 hours. After natural cooling, toluene is added, the first liquid is stirred, and ultraviolet rays of 275 to 320 nanometers are irradiated for 3 to 5 hours to obtain a second liquid; S3: The container is opened, pyridine and ammonium carbonate are added, and the mixture is stirred. The third liquid is stirred to obtain a third liquid; S4: the third liquid is kept at -70°C to -80°C, and a mixed gas of ozone and oxygen is bubbled in turn for 5 to 15 minutes, pure oxygen is bubbled for 1 to 5 minutes, and nitrogen is bubbled for 1 to 5 minutes to obtain a fourth liquid; S5: the fourth liquid is kept at 85 to 95°C and stirred for 12 to 36 hours, and filtered and dried to obtain a first powder; S1 to S5 are mainly to convert carbon atoms in H3BTT·2HCl into nitrogen atoms, which are part of the active sites and play a key role in the activity of the catalyst. First, the oxidative reconstruction of the benzene ring produces a ring-open intermediate with an electron affinity site, which is ready for ring closure and carbon-based leaving groups. An intermediate with two carbonyl groups is generated in situ, activated to form a carboxylate leaving group, and the activation promotes the condensation of ammonia to finally obtain the product. The benzene ring substituted with different groups at different positions is converted into the corresponding pyridine derivative in one step, thereby replacing carbon atoms with nitrogen atoms. This replacement method can control the amount of nitrogen doping and can effectively increase the content of nitrogen elements. In addition, pyridine derivatives have nitrogen atom types in various positions, including nitrogen atoms located at the edge of the carbon plane, each nitrogen atom of which is connected to two carbon atoms and donates a p electron to the aromatic p system, and nitrogen atom types connected to three carbon atoms, thereby increasing efficient electrocatalytic activity.
[0006] S6: Under a protective atmosphere, the first powder and anhydrous ferrous chloride are added to a mixture of dimethylformamide and dimethyl sulfoxide, and the mixture is stirred at 100-150°C for 12-36 hours, filtered, and dried to obtain a second powder; this step is to synthesize a metal organic material similar to ZIF, which has been combined with nitrogen atoms with chloride as the center, so that high-density nitrogen atom active sites are evenly distributed in the octahedron containing iron ions, and adjacent octahedrons share space to form a cubic framework.
[0007] S7: In a protective atmosphere, the second powder is kept at 700-1000°C for 60-180 minutes to obtain a ZIF-derived non-precious metal electrocatalyst. This step is to convert the organic ligand into a carbon carrier by thermal cracking to form a porous carbon skeleton, which not only improves the electronic conductivity, but also increases the degree of graphitization due to thermal decomposition, promotes the formation of nitrogen atom active sites at the edge of the carbon plane, promotes the generation of iron-nitrogen-carbon active sites, and improves the catalytic activity.
[0008] The method for preparing the ZIF-derived non-precious metal electrocatalyst according to the embodiment of the present application has at least the following beneficial effects:
[0009] By converting carbon atoms in H3BTT·2HCl into nitrogen atoms, carbon atoms are replaced by nitrogen atoms. This replacement method can control the amount of nitrogen doping and effectively increase the content of nitrogen. Nitrogen atoms are part of the active sites. At the same time, the ordered lattice of graphitized carbon can promote the formation of active sites generated by nitrogen doping, thereby increasing efficient electrocatalytic activity. Porous metal-organic framework materials are further synthesized, in which metal ions or metal clusters are connected together by organic linkers, and their three-dimensional crystalline structure can provide high-density active sites evenly distributed in the framework. The organic ligands are converted into carbon carriers by thermal decomposition to form iron / nitrogen / carbon active sites, so that active metal-containing substances and carbon carriers can be formed simultaneously. The porosity of the carbon produced by thermal cracking can ensure the accessibility of the active sites to the reactants and products related to ORR.
[0010] According to some embodiments of the present application, S7: in a protective atmosphere, the second powder is kept at 700-1000°C for 90 minutes to obtain a third powder; and further comprises: S8: adding the third powder to a sulfuric acid solution, ultrasonicating for 1-3 hours, filtering, washing, and drying to obtain a ZIF-derived non-precious metal electrocatalyst. The chemical pickling treatment is mainly to dissolve unstable iron atoms, avoid contaminating the proton exchange membrane during the catalytic reaction, and is beneficial to ensure the life of the fuel cell.
[0011] According to some embodiments of the present application, the concentration of the sulfuric acid solution is 0.5-2 mol / L.
[0012] According to some embodiments of the present application, the mass ratio of the first powder to anhydrous ferrous chloride is 1:3-4.
[0013] According to some embodiments of the present application, the mass ratio of H3BTT·2HCl, m-chloroperbenzoic acid, pyridine and ammonium carbonate is 250-350:300-400:0.5-2:500-600.
[0014] According to some embodiments of the present application, the concentration of ozone in the mixed gas of ozone and oxygen is 20% to 40%.
[0015] According to some embodiments of the present application, S4: place the container in an acetone, ether or ethyl acetate bath, and add dry ice or liquid nitrogen to keep the third liquid at (-70) ~ (-80) ° C, and successively introduce a mixed gas of ozone and oxygen for 5 to 15 minutes, introduce pure oxygen for 1 to 5 minutes, and introduce nitrogen for 1 to 5 minutes to obtain a fourth liquid.
[0016] According to some embodiments of the present application, S4: the third liquid is kept warm at -78°C, and a mixed gas of ozone and oxygen is bubbled in sequence for 10 minutes, pure oxygen is bubbled in for 3 minutes, and nitrogen is bubbled in for 3 minutes to obtain a fourth liquid.
[0017] According to some embodiments of the present application, in S2, the wavelength of the ultraviolet light is 390 nanometers.
[0018] According to some embodiments of the present application, a ZIF-derived non-precious metal electrocatalyst prepared by the above-mentioned ZIF-derived non-precious metal electrocatalyst is provided.
[0019] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present application is further described below in conjunction with the accompanying drawings and embodiments, wherein:
[0021] Figure 1 A schematic diagram of the process of ZIF-derived non-precious metal electrocatalyst according to an embodiment of the present application;
[0022] Figure 2 Schematic diagram of transmission electron microscopy (TEM) of the preparation method of the ZIF-derived non-precious metal electrocatalyst of Example 1 of the present application;
[0023] Figure 3 This is a cyclic voltammetry (CV) test graph of the ZIF-derived non-precious metal electrocatalyst prepared in Example 1 of the present application under acidic conditions. DETAILED DESCRIPTION
[0024] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0025] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0026] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0027] The following is a further description of the present invention, rather than a limitation of the present invention.
[0028] Example 1
[0029] like Figure 1 As shown, this embodiment prepares a ZIF-derived non-precious metal electrocatalyst, and the specific process is as follows:
[0030] (1) A flask was flame-dried, 290 mg of 1,3,5-tris(1H-tetrazol-5-yl)benzene hydrochloride (H3BTT·2HCl) and 3.5 ml of 0.31 mol / L chloroform were added to the flask, and then 464 mg of 75% by mass m-chloroperbenzoic acid was added dropwise to the flask to obtain a mixture, i.e., the first solution.
[0031] (2) Place a polytetrafluoroethylene magnetic stirring bar in the flask, seal the flask, and place it in a preheated oil bath. Stir the mixture at 50°C for 19 hours. After the mixture cools to room temperature, dilute it with 16.5 ml of 0.05 mol / L toluene. Irradiate the flask with a 390 nm LED light, and continue stirring and irradiating for 4 hours to obtain a mixture, i.e., the second solution.
[0032] (3) Turn off the light, open the flask, add 0.81 ml of pyridine and 546 mg of ammonium carbonate to the second liquid, and obtain a mixture, namely the third liquid. Place the flask in an acetone bath, add liquid nitrogen to cool the third liquid to -78°C, and ventilate with a mixed gas containing 30% ozone and oxygen for 10 minutes, then ventilate with pure oxygen for 3 minutes, and finally ventilate with nitrogen for 3 minutes. Open the flask and stir at room temperature for 15 minutes to obtain a mixture, namely the fourth liquid.
[0033] (4) The flask was sealed and placed in a preheated oil bath. After stirring at 90° C. for 24 hours until the precipitation was complete, the flask was filtered and then placed in an electric constant temperature forced air drying oven at 80° C. for 4 hours to obtain a first powder.
[0034] (5) Under argon atmosphere, 122 mg of the first powder and 380 mg of anhydrous ferrous chloride were added to a mixture of 40 mL of dimethylformamide and 40 mL of dimethyl sulfoxide, reacted at 110° C. for 24 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven and dried at 80° C. for 4 hours to obtain a second powder.
[0035] (6) The second powder was placed in a quartz tube, and the temperature was increased to 700° C. at a heating rate of 1° C. / min and an argon flow rate of 20 mL / min for 90 minutes in an argon atmosphere to obtain a third powder.
[0036] (7) The third powder was added to a 1 mol / L sulfuric acid solution, subjected to ultrasonic treatment for 2 hours, and then continuously stirred at 80° C. for 20 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven and dried at 80° C. for 4 hours to obtain a fourth powder.
[0037] Example 2
[0038] This embodiment prepares a method for preparing a ZIF-derived non-precious metal electrocatalyst, and the specific process is as follows:
[0039] (1) A flask was flame-dried, 250 mg of 1,3,5-tris(1H-tetrazol-5-yl)benzene hydrochloride and 3.5 ml of 0.31 mol / L chloroform were added to the flask, and then 400 mg of 75% by mass m-chloroperbenzoic acid was added dropwise to the flask to obtain a mixture, i.e., the first solution.
[0040] (2) Place a polytetrafluoroethylene magnetic stirring bar in the flask, seal the flask, and place it in a preheated oil bath. Stir the mixture at 40°C for 20 hours. After the mixture cools to room temperature, dilute it with 16.5 ml of 0.05 mol / L toluene. Irradiate the flask with a 390 nm LED light, and continue stirring and irradiating for 3 hours to obtain a mixture, i.e., the second solution.
[0041] (3) Turn off the light, open the flask, add 0.5 ml of pyridine and 500 mg of ammonium carbonate to the second liquid, and the resulting mixture is the third liquid. Place the flask in an ether bath, add liquid nitrogen to cool the third liquid to -70°C, and ventilate with a mixed gas containing 20% ozone and oxygen for 15 minutes, then ventilate with pure oxygen for 5 minutes, and finally ventilate with nitrogen for 5 minutes. Open the flask and stir at room temperature for 15 minutes to obtain a mixture, which is the fourth liquid.
[0042] (4) The flask is sealed and placed in a preheated oil bath. After stirring at 85° C. for 24 hours until precipitation is complete, the flask is filtered and then placed in an electric constant temperature forced air drying oven at 80° C. for 4 hours to obtain a first powder.
[0043] (5) Under argon atmosphere, 122 mg of the first powder and 366 mg of anhydrous ferrous chloride were added to a mixture of 40 mL of dimethylformamide and 40 mL of dimethyl sulfoxide, reacted at 100° C. for 24 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven and dried at 80° C. for 4 hours to obtain a second powder.
[0044] (6) The second powder was placed in a quartz tube, and the temperature was increased to 800° C. at a heating rate of 1° C. / min and an argon flow rate of 20 mL / min for 90 minutes in an argon atmosphere to obtain a third powder.
[0045] (7) The third powder was added to a 0.5 mol / L sulfuric acid solution, subjected to ultrasonic treatment for 3 hours, and then continuously stirred at 80° C. for 20 hours, filtered, washed with deionized water, and then placed in an electric constant temperature blast drying oven and dried at 80° C. for 4 hours to obtain a fourth powder.
[0046] Example 3
[0047] This embodiment prepares a method for preparing a ZIF-derived non-precious metal electrocatalyst, and the specific process is as follows:
[0048] (1) A flask was flame-dried, 300 mg of 1,3,5-tris(1H-tetrazol-5-yl)benzene hydrochloride and 3.5 ml of 0.31 mol / L chloroform were added to the flask, and then 440 mg of 75% by mass m-chloroperbenzoic acid was added dropwise to the flask to obtain a mixture, i.e., the first solution.
[0049] (2) Place a polytetrafluoroethylene magnetic stirring bar in the flask, seal the flask, and place it in a preheated oil bath. Stir the mixture at 45°C for 18 hours. After the mixture cools to room temperature, dilute it with 16.5 ml of 0.05 mol / L toluene. Irradiate the flask with a 390 nm LED light, and continue stirring and irradiating for 3.5 hours to obtain a mixture, i.e., the second solution.
[0050] (3) Turn off the light, open the flask, add 1 ml of pyridine and 560 mg of ammonium carbonate to the second liquid, and the resulting mixture is the third liquid. Place the flask in an ethyl acetate bath, add liquid nitrogen to cool the third liquid to -75°C, and ventilate with a mixed gas of 25% ozone and oxygen for 12 minutes, then ventilate with pure oxygen for 4 minutes, and finally ventilate with nitrogen for 4 minutes. Open the flask and stir at room temperature for 15 minutes to obtain a mixture, which is the fourth liquid.
[0051] (4) The flask was sealed and placed in a preheated oil bath. After stirring at 87° C. for 24 hours until the precipitation was complete, the flask was filtered and then placed in an electric constant temperature forced air drying oven at 80° C. for 4 hours to obtain a first powder.
[0052] (5) Under argon atmosphere, 122 mg of the first powder and 244 mg of anhydrous ferrous chloride were added to a mixture of 40 mL of dimethylformamide and 40 mL of dimethyl sulfoxide, reacted at 120° C. for 24 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven and dried at 80° C. for 4 hours to obtain a second powder.
[0053] (6) The second powder was placed in a quartz tube, and the temperature was increased to 900° C. at a rate of 1° C. / min, and heat treated in an argon atmosphere at a flow rate of 20 mL / min for 90 minutes to obtain a third powder.
[0054] (7) The third powder was added to a 0.7 mol / L sulfuric acid solution, subjected to ultrasonic treatment for 2.5 hours, and then continuously stirred at 80° C. for 20 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven and dried at 80° C. for 4 hours to obtain a fourth powder.
[0055] Example 4
[0056] This embodiment prepares a method for preparing a ZIF-derived non-precious metal electrocatalyst, and the specific process is as follows:
[0057] (1) A flask was flame-dried, 330 mg (1.0 mmol) of 1,3,5-tris(1H-tetrazol-5-yl)benzene hydrochloride and 3.5 ml of 0.31 mol / L chloroform were added to the flask, and then 480 mg of 75% by mass m-chloroperbenzoic acid was added dropwise to the flask to obtain a mixture, i.e., the first solution.
[0058] (2) A polytetrafluoroethylene magnetic stirring bar was placed in the flask, the flask was sealed, and the mixture was placed in a preheated oil bath. The mixture was stirred at 55° C. for 17 hours. After the mixture was cooled to room temperature, it was diluted with 16.5 ml of 0.05 mol / L toluene. The flask was irradiated with a 275 nm LED light, and the mixture was continuously stirred and irradiated for 4.5 hours to obtain a mixture, i.e., the second solution.
[0059] (3) Turn off the light, open the flask, add 1.5 ml of pyridine and 580 mg of ammonium carbonate to the second liquid, and the resulting mixture is the third liquid. Place the flask in an acetone bath, add dry ice to cool the third liquid to -80°C, and ventilate with a mixed gas containing 35% ozone and oxygen for 7 minutes, then ventilate with pure oxygen for 2 minutes, and finally ventilate with nitrogen for 2 minutes. Open the flask and stir at room temperature for 15 minutes to obtain a mixture, which is the fourth liquid.
[0060] (4) The flask was sealed and placed in a preheated oil bath. After stirring at 93° C. for 36 hours until the precipitation was complete, the flask was filtered and then placed in an electric constant temperature forced air drying oven at 80° C. for 4 hours to obtain the first powder.
[0061] (5) Under argon atmosphere, 122 mg of the first powder and 427 mg of anhydrous ferrous chloride were added to a mixture of 40 mL of dimethylformamide and 40 mL of dimethyl sulfoxide, reacted at 140° C. for 36 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven and dried at 80° C. for 4 hours to obtain a second powder.
[0062] (6) The second powder was placed in a quartz tube, and heat treated in an argon atmosphere at a heating rate of 1°C / min to 1000°C and an argon flow rate of 20 mL / min for 180 minutes to obtain a third powder.
[0063] (7) The third powder was added to a 1.5 mol / L sulfuric acid solution, ultrasonically treated for 1.5 hours, and then continuously stirred at 80° C. for 20 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven at 80° C. for 4 hours to obtain a fourth powder.
[0064] Example 5
[0065] This embodiment prepares a method for preparing a ZIF-derived non-precious metal electrocatalyst, and the specific process is as follows:
[0066] (1) A flask was flame-dried, 350 mg of 1,3,5-tris(1H-tetrazol-5-yl)benzene hydrochloride and 3.5 ml of 0.31 mol / L chloroform were added to the flask, and then 533 mg of 75% by mass m-chloroperbenzoic acid was added dropwise to the flask to obtain a mixture, i.e., the first solution.
[0067] (2) Place a polytetrafluoroethylene magnetic stirring bar in the flask, seal the flask, and place it in a preheated oil bath. Stir the mixture at 60°C for 15 hours. After the mixture cools to room temperature, dilute it with 16.5 ml of 0.05 mol / L toluene. Irradiate the flask with a 400 nm LED light, and continue stirring and irradiating for 5 hours to obtain a mixture, i.e., the second solution.
[0068] (3) Turn off the light, open the flask, add 2 ml of pyridine and 600 mg of ammonium carbonate to the second liquid, and the resulting mixture is the third liquid. Place the flask in an ether bath, add dry ice to cool the third liquid to -77°C, and ventilate with a mixed gas containing 40% ozone and oxygen for 5 minutes, then ventilate with pure oxygen for 1 minute, and finally ventilate with nitrogen for 1 minute. Open the flask and stir at room temperature for 15 minutes to obtain a mixture, which is the fourth liquid.
[0069] (4) The flask was sealed and placed in a preheated oil bath. After stirring at 95° C. for 12 hours until the precipitation was complete, the flask was filtered and then placed in an electric constant temperature forced air drying oven at 80° C. for 4 hours to obtain a first powder.
[0070] (5) Under argon atmosphere, 122 mg of the first powder and 488 mg of anhydrous ferrous chloride were added to a mixture of 40 mL of dimethylformamide and 40 mL of dimethyl sulfoxide, reacted at 150° C. for 12 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven and dried at 80° C. for 4 hours to obtain a second powder.
[0071] (6) The second powder was placed in a quartz tube, and heat treated in an argon atmosphere at a heating rate of 1°C / min to 1000°C and an argon flow rate of 20 mL / min for 60 minutes to obtain a third powder.
[0072] (7) The third powder was added to a 2 mol / L sulfuric acid solution, ultrasonically treated for 1 hour, and then continuously stirred at 80° C. for 20 hours, filtered, washed with deionized water, and then placed in an electric constant temperature forced air drying oven at 80° C. for 4 hours to obtain a fourth powder.
[0073] Working principle:
[0074] By converting the carbon atoms in H3BTT·2HCl into nitrogen atoms, the oxidative reconstruction of the benzene ring first produces a ring-open intermediate with an electron affinity site, which is ready for ring closure and carbon-based leaving groups, and in situ generates an intermediate with two carbonyl groups, which is activated to form a carboxylate leaving group. At the same time, the activation promotes the condensation of ammonia and finally obtains the product, and the benzene rings substituted with different positions and different groups are converted into the corresponding pyridine derivatives in one step, thereby replacing carbon atoms with nitrogen atoms. This replacement method can control the amount of nitrogen doping and effectively increase the content of nitrogen elements. Nitrogen atoms are part of the active site and play a key role in the activity of the catalyst. This method increases the types of nitrogen atoms at various positions, including nitrogen atoms at the edge of the carbon plane, each of which is connected to two carbon atoms and donates a p electron to the aromatic p system, and nitrogen atoms connected to three carbon atoms, thereby increasing efficient electrocatalytic activity. After that, a porous metal-organic framework material is further synthesized, in which metal ions or metal clusters are connected together by organic linkers, and its main building block is a truncated octahedron, and adjacent octahedrons share square faces in space to form a cubic framework. Chloride is centered and combined with nitrogen atoms from four different ligands. The homogeneous phase of the polyhedral shaped particles is similar to ZIF-8 crystals, but the surface and edges are rougher. Due to its three-dimensional crystalline structure, it can provide a high density of active sites evenly distributed in the framework. The organic ligands are further converted into carbon carriers by thermal decomposition, so that active metal-containing substances and carbon carriers can be formed simultaneously. The porosity of the carbon produced by thermal cracking can ensure the accessibility of the active sites to the reactants and products related to ORR. First, it is thermally cracked under a protective gas flow to form iron / nitrogen / carbon active sites. During the thermal cracking process, the synthesized organic part will be carbonized to generate carbon, thereby providing the required electronic conductivity. And the degree of graphitization is increased by pyrolysis, thereby increasing the density of active sites. The ordered lattice of graphitized carbon can promote the formation of active sites generated by nitrogen doping and increase the electronic conductivity of the catalyst. At the same time, the microporous structure is further developed during the heat treatment. Most of the iron is dissolved during the chemical pickling process. It can avoid the contamination of the proton exchange membrane caused by unstable iron-containing species in an acidic environment, thereby increasing the life of the fuel cell.
[0075] The preparation method of ZIF-derived non-precious metal electrocatalysts was tested, and the results were as follows Figures 2 to 3 shown.
[0076] The test was carried out on a rotating disk electrode and an electrochemical workstation. The working electrode was a glassy carbon electrode, the reference electrode was a Hg / HgSO4 electrode, and the counter electrode was a platinum wire. The electrolyte solution was 0.1M perchloric acid (under oxygen saturation conditions). The test method was linear sweep voltammetry, and the test process was completed at room temperature and pressure.
[0077] like Figure 3 As shown, under acidic conditions, the electrode made of the ZIF-derived non-precious metal electrocatalyst in Example 1 has a starting potential of 0.96 V (vs. RHE), a half-wave potential of 0.82 V (vs. RHE), and a mass activity of 4.74 A / g (@0.8 V vs. RHE), reaching the average activity level of currently reported non-precious metal catalysts for fuel cells under acidic test conditions.
[0078] The embodiments of the present application are described in detail above in conjunction with the accompanying drawings, but the present application is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0079] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.
[0080] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a ZIF-derived non-precious metal electrocatalyst, characterized in that: include: S1: adding H3BTT·2HCl and chloroform into a container under a protective atmosphere, and dropping m-chloroperbenzoic acid into the container to obtain a first liquid; S2: sealing the container, keeping it warm at 40° C. to 60° C., stirring the first liquid for 15 to 20 hours, naturally cooling it, adding toluene, stirring the first liquid, and irradiating it with 275 to 400 nm ultraviolet rays for 3 to 5 hours to obtain a second liquid; S3: opening the container, adding pyridine and ammonium carbonate, and stirring to obtain a third liquid; S4: keeping the third liquid at -70°C to -80°C, sequentially introducing a mixed gas of ozone and oxygen for 5 to 15 minutes, introducing pure oxygen for 1 to 5 minutes, and introducing nitrogen for 1 to 5 minutes to obtain a fourth liquid; S5: keeping the fourth liquid at 85-95° C. and stirring for 12-36 hours, filtering and drying to obtain a first powder; S6: under a protective atmosphere, adding the first powder and anhydrous ferrous chloride to a mixture of dimethylformamide and dimethyl sulfoxide, stirring at 100 to 150° C. for 12 to 36 hours, filtering, and drying to obtain a second powder; S7: Under a protective atmosphere, keeping the second powder at 700-1000° C. for 60-180 minutes to obtain the ZIF-derived non-precious metal electrocatalyst.
2. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to claim 1, characterized in that: The S7: in a protective atmosphere, keeping the second powder at 700-1000° C. for 90 minutes to obtain a third powder; and also includes: S8: adding the third powder into a sulfuric acid solution, ultrasonicating for 1-3 hours, filtering, washing, and drying to obtain the ZIF-derived non-precious metal electrocatalyst.
3. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to claim 2, characterized in that: The concentration of the sulfuric acid solution is 0.5-2 mol / L.
4. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to claim 1, characterized in that: The mass ratio of the first powder to the anhydrous ferrous chloride is 1:3-4.
5. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to claim 1, characterized in that: The mass ratio of the H3BTT·2HCl, the m-chloroperbenzoic acid, the pyridine and the ammonium carbonate is 250-350:300-400:0.5-2:500-600.
6. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to claim 1, characterized in that: The concentration of ozone in the mixed gas of ozone and oxygen is 20% to 40%.
7. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to claim 1, characterized in that: S4: placing the container in an acetone, ether or ethyl acetate bath, and adding dry ice or liquid nitrogen to keep the third liquid at (-70) to (-80)°C, and sequentially bubbling a mixed gas of ozone and oxygen for 5 to 15 minutes, bubbling pure oxygen for 1 to 5 minutes, and bubbling nitrogen for 1 to 5 minutes to obtain the fourth liquid.
8. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to claim 1, characterized in that: The S4: the third liquid is kept warm at -78°C, and a mixed gas of ozone and oxygen is bubbled in sequence for 10 minutes, pure oxygen is bubbled in for 3 minutes, and nitrogen is bubbled in for 3 minutes to obtain the fourth liquid.
9. The method for preparing a ZIF-derived non-noble metal electrocatalyst according to any one of claims 1 to 8, characterized in that: In S2, the wavelength of the ultraviolet light is 390 nanometers.
10. A ZIF-derived non-precious metal electrocatalyst prepared according to the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Novel materials and their use for the electrocatalytic evolution or uptake of h2
CN102224624A
Non-Noble Metal Electrocatalysts for Oxygen Depolarized Cathodes and Their Uses
US20150340705A1